2021
DOI: 10.1159/000512953
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Imaging Features and Postnatal Outcome of Short Corpus Callosum: A Series of 42 Cases

Abstract: Objectives: Our goal was to provide a better understanding of isolated short corpus callosum (SCC) regarding prenatal diagnosis and postnatal outcome. Methods: We retrospectively reviewed prenatal and postnatal imaging, clinical, and biological data from 42 cases with isolated SCC. Results: Prenatal imaging showed SCC in all cases (n = 42). SCC was limited to rostrum and/or genu and/or splenium in 21 cases, involved body in 16 cases, and was more extensive in 5 cases. Indirect imaging features included typical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…IHC and PL are known to cause obstruction of the commissural fibers responsible for the abnormalities of the CC. 43 These abnormalities carry a better prognosis, 21,44 which is in keeping with the absence of pES abnormality. The diagnosis of PL is suspected on US in cases of pericallosal hyperechogenicity associated with the abnormalities of the CC.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…IHC and PL are known to cause obstruction of the commissural fibers responsible for the abnormalities of the CC. 43 These abnormalities carry a better prognosis, 21,44 which is in keeping with the absence of pES abnormality. The diagnosis of PL is suspected on US in cases of pericallosal hyperechogenicity associated with the abnormalities of the CC.…”
Section: Discussionmentioning
confidence: 85%
“…We recently evaluated the contribution of pES for the diagnostic work-up of abnormalities of the CC. 18 In addition to genetic abnormalities, it has been suggested that the type of abnormality of the CC could also impact the prognosis, 1,[19][20][21] but due to different and unclear definitions in the literature, this point needs to be clarified. Thus, prenatal imaging and genetic testing are pivotal for prenatal counseling to better inform patients about the neurodevelopmental prognosis as early as possible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reference charts for fetal CC length based on gestational age can be found elsewhere 17,19 . Short CC is defined as reduced CC length, less than or equal to the first percentile 20 …”
Section: Normal Appearance Of CC In Prenatal Us and Mrimentioning
confidence: 99%
“…17,19 Short CC is defined as reduced CC length, less than or equal to the first percentile. 20 New methods are also proposed to determine the normality of CC length without using reference charts for gestational age. The ratio between the CC length and the internal cranial occipitofrontal dimension (ICOFD/CC) is unchanged during a normal pregnancy (2.35 ± 0.11) and this ratio is increased (mean ratio: 3.20 ± 0.84) in fetuses with short CC.…”
Section: Normal Appearance Of CC In Prenatal Us and Mrimentioning
confidence: 99%